2014
DOI: 10.1002/dys.1484
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusion of Students with Dyslexia in Higher Education: A Systematic Review Using Narrative Synthesis

Abstract: This article reports on a study focusing on the inclusion of students with dyslexia in higher education (HE). A systematic review was carried out to retrieve, critically appraise and synthesize the available evidence on how the inclusion of students with dyslexia can be fostered in HE. The 15 studies included in the final synthesis employed descriptive designs and overwhelmingly used qualitative methods to explore dyslexic students' perceptions on the impact of teaching, support and accommodation in their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
134
0
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(152 citation statements)
references
References 22 publications
(23 reference statements)
5
134
0
13
Order By: Relevance
“…Positive themes included appreciation for engaging speaking style and flexible lecture formats, deep engagement with learning tasks and use of many self‐directed learning strategies that could be viewed as strengths. These findings are consistent with those of previous researchers (Kirby et al ., ; Pino & Mortari, ; Olofsson, Taube, and Ahl, ), who found that students with dyslexia used deep learning strategies more often than their non‐dyslexic peers and used more study aids and coping strategies. These types of characteristics and behaviours tend to be highly sought after in workplaces.…”
Section: Discussionmentioning
confidence: 99%
“…Positive themes included appreciation for engaging speaking style and flexible lecture formats, deep engagement with learning tasks and use of many self‐directed learning strategies that could be viewed as strengths. These findings are consistent with those of previous researchers (Kirby et al ., ; Pino & Mortari, ; Olofsson, Taube, and Ahl, ), who found that students with dyslexia used deep learning strategies more often than their non‐dyslexic peers and used more study aids and coping strategies. These types of characteristics and behaviours tend to be highly sought after in workplaces.…”
Section: Discussionmentioning
confidence: 99%
“…Although inclusive policies and legislation are in place, the elimination of barriers to participation in upper secondary school depends largely on a schools' resources and teachers' knowledge of how to support students with SEN (Pearce, Gray, and CampbellEvans 2010). For example, several studies have reported that adolescent students with neuropsychiatric disorders (Bolic Baric et al 2016;Sikirica et al 2015;Fleischer Simmeborn, Adolfsson, and Granlund 2013) and dyslexia (Gibson and Kendall 2010;Pino and Mortari 2014) experience school failures and restricted participation since their needs for support are not recognised by the educational services. A qualitative study including adolescents with ADHD and their caregivers from eight European countries showed that about 50% of the students received accommodations in school, such as extra attention from teachers, adapted homework assignments or special classes.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the inclusion of students with dyslexia revealed that these were not always provided with accommodations or aware of their right of support. Moreover, students emphasised that the need for support was individual and varied in different settings (Pino and Mortari 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not the intention, squabbles in the field of dyslexia research feed arguments expressed in the popular press that dyslexia does not exist (for example, Sample 2005), which unfortunately are too often translated into an assumption that people's reports of specific difficulties with literacy and related domains are disingenuous Variations in ways in which the dyslexia label may be interpreted can also mean that students have to be increasingly flexible in how they use the label: sometimes hiding it, sometimes openly disclosing, sometimes taking pride in it, sometimes feeling ashamed to take help (Cameron and Billington 2015b;Pollak 2005). Yet there is strong evidence that people with the dyslexia label do face particular difficulties in relation to specific difficulties in particular cognitive domains (for example, Nicolson and Fawcett 2008;Shaywitz and Shaywitz 2005;Snowling 1995;Stein 2001) and that these have implications for study in higher education (Farmer, riddick, and Sterling 2002;Hatcher, Snowling, and Griffiths 2002;Mortimore and Crozier 2006;Pino and Mortari 2014). There is also evidence that dyslexic adults have lower self-esteem in educational contexts (Carroll and Iles 2006;Madriaga 2007;Riddick et al 1999), and often have to manage memories of very challenging experiences at school which continue to impact upon their adult educational experiences (for example , Madriaga 2007;Mcnulty 2003).…”
Section: Introduction and Literaturementioning
confidence: 99%